PEMBELAJARAN PEMAHAMAN KONSEP IPS MELALUI PENERAPAN METODE ACTIVE LEARNING TIPE INDEX CARD MATCH PADA SISWA KELAS IV - Hendra Yadi Atmanegara; Galih Dani Septiyan Rahayu (IKIP Siliwangi, 2022)
This study aims to examine learning social studies understanding in grade IV students using the index card type active learning method. The research method used is descriptive qualitative. The subjects in this study were fourth grade students of SD Negeri 259 Griba, Bandung City with a total of 30 students consisting of 11 male students and 19 female students. The instruments used were teacher and student observation sheets, questions about economic activities, and teacher and student questionnaires. The results showed that there was an increase in the quality of learning after using the index card type active learning method. This is indicated by the average value of class social studies understanding of 90.00% which is in the good category, the highest score of students is 96 and the lowest score is 40. Students' learning completeness shows that 90.00% of students get scores above the minimum completeness criteria, and 10% still scored below the minimum completeness criteria value.